Anthocyanin Protects Cardiac Function and Cardiac Fibroblasts From High-Glucose Induced Inflammation and Myocardial Fibrosis by Inhibiting IL-17 - Er Yue; Yahan Yu; Xinyao Wang; Bing Liu; Bing Liu; Yunlong Bai; Yunlong Bai; Baofeng Yang; Baofeng Yang (Frontiers Media S.A., 2021)
Diabetic cardiomyopathy (DCM) is one of the major causes of death in diabetic patients. Its pathogenesis involves inflammation and fibrosis that damages the heart tissue and impairs cardiac function. Interleukin (IL)-17, a pro-inflammatory cytokine that plays an important role in a variety of chronic inflammatory processes can serve as an attractive therapeutic target. Anthocyanin, a water-soluble natural pigment, possesses impressive anti-inflammatory activity. However, its role in DCM is unclear. Hence, we investigated the protective effect of anthocyanin on the cardiovascular complications of diabetes using a mouse type 1 diabetes mellitus model induced by streptozotocin. Cardiac function and structural alterations in diabetic mice were tested by echocardiography, hematoxylin and eosin staining, and Masson trichrome staining. Immunohistochemistry was performed to evaluate the distribution and deposition of IL-17 and collagen I and III from the left ventricular tissues of diabetic mice. Cell viability was measured using the methyl thiazolyl tetrazolium assay. Protein levels of IL-17, tumor necrosis factor α, IL-1β, and IL-6 were determined using enzyme-linked immunosorbent assay. IL-17 and collagen I and III were detected by western blotting and immunofluorescence, and their mRNA levels were quantified using quantitative reverse transcription PCR. We observed that anthocyanin lowered blood glucose, improved cardiac function, and alleviated inflammation and fibrosis in the heart tissue of diabetic mice. Meanwhile, anthocyanin reduced the expression of IL-17 in high-glucose-treated cardiac fibroblasts and exhibited an anti-inflammatory effect. Deposition of collagen I and III was also decreased by anthocyanin, suggesting that anthocyanin contributes to alleviating myocardial fibrosis. In summary, anthocyanin could protect cardiac function and inhibit IL-17-related inflammation and fibrosis, which indicates its therapeutic potential in the treatment of diabetes mellitus-related complications.